Novel variant in the leptin receptor (LEPR) gene and its association with fat quality, odour and flavour in sheep - A. Gunawan; F. W. Pramukti; K. Listyarini; M. A. Abuzahra; J. Jakaria; C. Sumantri; I. Inounu; M. J. Uddin (Diponegoro University, 2019)
The aim of this study was to investigate the association and expression of LEPR with fat quality, flavour and odour in sheep. A total of 47 rams were used in this study. Fatty acids composition, BCFA (Branch Chanin Fatty Acids; MNA, MP, MOA, and EOA) and skatole (MI) representing fat quality, flavour and odour in sheep were measured at ages of 10-12 months old. Identification of novel variant and expression analysis of LEPR gene with different fat quality, odour and flavour were performed by PCR RFLP and qRT-PCR, respectively. A SNP in genomic region g.40854778 A>C of the LEPR gene was associated (P<0.05) with fat quality of saturated fatty acids (SFA) including [tricosanoic acid (C23:0) and tetracosanoic acid (C24:0)] and poly unsaturated fatty acid (PUFA) [docosahexaenoic acid (C22:6n3)]. However, the novel variant of LEPR was not significantly associated (P<0.05) with fat content, odour and flavour (MNA, MP, MOA, EOA, and MI). The mRNA expression analysis showed that LEPR mRNA expression was higher (P<0.01) in sheep found at the AA genotype. It could be concluded that variant SNP in the LEPR may contribute to fatty acid composition without influencing odour and flavour traits in sheep.